Assessing the performance of five adult mosquito sampling methods for malaria vector surveillance in various ecosystems in Cameroon - Nwane, Philippe; Piameu, Michael; Emalio, Yannick Niamsi; Ekoko, Wolfgang Eyisap; Mandeng, Stanislas Elysée; Mbakop, Lili Ranaise; Patchoke, Salomon; Toto, Jean-Claude; Alenou, Leo Dilane; Bikoi, Elisabeth Ngo; Onguina, Hugues; Nvondo, Narcisse; et al. (Frontiers in Tropical Diseases, 2024)
Many sampling methods are used for entomological surveillance of vector borne diseases. This paper, evaluated the performance of five methods with regard to various ecosystems encountered in Cameroon. Two entomological databases generated during 2011-2014 in the North Region, and 2018-2019 in the Centre Region were examined. Mosquitoes were collected using the « human landing catches » (HLC) and four conventional methods including Clay Pots (CPs), Pyrethroid Spray Catches (PSCs), Window Exit Traps (WETs) and Centers for Disease Control-Light Traps (CDC-LTs) for which the performance were assessed in this study. A total of 29 anophelines were identified from samples collected during the two studies. All these anophelines were found in North region, with 5 species including An. gambiae s.l, An. funestus, An. rufipes, An. paludis and An. pharoensis being the most abundant and prevalent in the prospected HDs. In the Centre region, only five species including An. gambiae s.l, An. funestus, An. coustani, An. ziemanni and An. paludis were recorded. Among these, An. gambiae s.l was the most abundant and prevalent species in the surveyed HDs. Data confirmed HLC as the best in sampling outdoor and indoor mosquitoes in the surveyed HDs. The conventional methods showed variable records regarding the species richness across the surveyed HDs. Based on the species richness WET appeared as an alternative to HLC in sampling outdoor mosquitoes in Garoua and Mayo Oulo HDs, and CP was the best alternative in Pitoa HD. In the Centre region CDC-LT was an alternative for outdoor and indoor collections in Nkolbisson HD, and the best alternative in outdoor collection in Ekie HD. Regarding the number of mosquitoes collected, CP was an alternative to HLC in outdoor collections in Garoua and Pitoa HDs, while WET was an alternative in Mayo Oulo HD. In the Centre region, CDC-LT was an alternative to HLC for indoor collections in Ekié and Nkolbisson HDs, while PSC proved to be the best alternative Nkolondom HD. These data are useful for the malaria entomological surveillance in the surveyed HDs. Similar investigations should be conducted in diverse ecosystems to ensure a better malaria entomological surveillance in Cameroon .